LONG TERM EFFICACY AND SAFETY OF ADALIMUMAB IN JUVENILE IDIOPATHIC ARTHRITIS (JIA) ASSOCIATED UVEITIS - lazarevic, dragana; Ratković-Janković, Marija; Jakovljević, Milica; vojinović, jelena (Acta medicae Medianae, 2021)
In the last decade tumor necrosis factor-α (TNF-α) inhibitors have shown excellent control of ocular inflammation in juvenile idiopathic arthritis (JIA) associated uveitis. We have retrospectively evaluated the long-term efficacy and safety of adalimumab in 19 biologically naive patients with JIA-associated uveitis from our biologic registry. Demographic data and blood samples were collected at different time points. Uveitis activity was evaluated by slit-lamp biomicroscopy. Adverse events were recorded.            Registry records provided 10 years follow up of 11 (57.90%) female patients  diagnosed as oligo/extended oligoarticular JIA with uveitis and 8 (42.10%) males diagnosed as enthesitis related arthritis (ERA) with uveitis. Adalimumab was the first biologics prescribed in JIA patients with active uveitis failed to respond to standard treatment. Ten years long follow up period have showed that there were no new relapsis of uveitis while patients were receiving adalimumab and metotrexate. All of our patients after adalimumab introduction were able to gradually tapper and stop treatment with topical steroids. 36.84% of our patients were able to stop biological treatment 36 months after adalimumab commencing. Uveitis has relapsed three monts after the adalimumab discontinuation only in two patients. No serious adverse events were recorded. 31,58% patients expirienced minor adverse events.            During the long term follow up period adalimumab have shown good efficacy and safety profile in JIA patients with active inflammatory ocular disease.